2000
DOI: 10.1016/s0020-7519(00)00047-3
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasite species richness and genetic variation among freshwater fish species: cause or consequence?

Abstract: The factors responsible for the maintenance of genetic variation among natural populations remain a mystery. Recent models of host±parasite co-evolution assume that parasites exert frequency-dependent selection on their hosts by favouring rare alleles that may confer resistance against infection. We tested this prediction in a comparative analysis that sought relationships between levels of genetic variation and the number of metazoan parasite species exploiting each host species. We used data on 40 species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The all-female clonal populations could also be classified as vulnerable, since antigen recognition and killing by T-cells is genetically restricted by the major histocompatibility complex (MHC) (Somamoto et al 2009). Lower tolerance to parasites has been reported in gynogens (Lively et al 1990, Moritz et al 1991, Poulin et al 2000, Hakoyama et al 2001.…”
Section: Introductionmentioning
confidence: 93%
“…The all-female clonal populations could also be classified as vulnerable, since antigen recognition and killing by T-cells is genetically restricted by the major histocompatibility complex (MHC) (Somamoto et al 2009). Lower tolerance to parasites has been reported in gynogens (Lively et al 1990, Moritz et al 1991, Poulin et al 2000, Hakoyama et al 2001.…”
Section: Introductionmentioning
confidence: 93%
“…However, this approach has to our knowledge never been applied to phenotypic traits implied in the encounter probability between hosts and parasites (Combes 1998). The possibility of reciprocal eVects of host's traits linked to the encounter rate and parasite infection seems highly probable given that genetic parameters and other intrinsic parameters, such as age, sex or hormonal levels of the host, have been found to inXuence infection probabilities (Paterson et al 1998;Poulin 1998;Poulin et al 2000;Krasnov et al 2005;Seivwright et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Ligophorus/Mugilidae specificity suggests that this is an association that results from a long coevolutionary process Suriano 1977, Marchiori et al 2015). In addition, studies have shown that long coevolutionary relationships can influence pathogenicity of the parasite, which certainly reflects selection processes of the host populations (Poulin et al 2000). Other authors showed this phenomena, even in high prevalence and intensity of infestation by Ligophorus spp.…”
Section: Species Of Ligophorusmentioning
confidence: 96%